Outcomes of drug coated balloon only angioplasty for stable angina in routine clinical practice. (3rd October 2022) - Merinopoulos, I; Gunawardena, T; Corballis, N; Gilbert, T; Maart, C; Reinhold, J; Ryding, A; Sarev, T; Sawh, C; Sulfi, S; Wickramarachchi, U; Wistow, T; et al.
Abstract: Introduction: The recent BASKETSMALL2 trial demonstrated safety and efficacy of drug coated balloon (DCB) angioplasty for de novo small vessel disease. Registry data have demonstrated that DCB angioplasty is safe; however, the majority of these studies are limited due to long recruitment time and small number of patients with DCB compared to drug eluting stents (DES). Our aim was to investigate if DCB-only strategy is safe to incorporate in routine clinical practice. Methods: We identified all patients treated for stable angina and de novo disease in our institution from January 2015 till November 2019. During that period an equivalent number of patients were treated with DCB-only or DES-only strategy on a yearly basis. The primary endpoint was all cause mortality. The secondary endpoints were cardiovascular mortality, acute coronary syndrome (ACS), ischaemic stroke, major bleeding and target lesion revascularisation (TLR). Data were obtained from the hospital episodes statistics from NHS digital. Clinical and angiographic data were collected from our prospectively collated database and supplemented from electronic records as required. All angiograms were reviewed to confirm accuracy of angiographic data and determine TLR. On multivariable COX regression analysis (Table 1) age, frailty and hypercholesterolaemia were the only independent predictors of all cause mortality. Results: A total of 1302 patients were identified. HES data were not obtained for 65 patients who had opted-out, therefore 1237 were included in the analysis; 544 were treated with DCB and 693 with DES. The average age for the DCB-group was 67.9±10.2 years old (79% male); while for the DES group it was 67.9±9.7 years old (78.1% male). The average follow up was 1339±514 days and 1354±527 days for the DCB and DES group respectively. Table 1 shows the differences between the groups in terms of clinical and angiographic characteristics. The DES group had more patients with history of COPD (6.3% vs 3%; p=0.01) and larger average vessel diameter (3.46±0.58 vs 3.09±0.53mm; p<0.001). The DCB group had more patients with true bifurcation disease and TIMI 0 or 1 pre-PCI (11.6% vs 8.1%; p=0.04) and TIMI 0 or 1 pre-PCI (11.7% vs 6.6%; p=0.001). Furthermore, more than 70% of patients in the DCB group had vessel diameter ≥3mm indicating that large vessels were treated. The all cause mortality was 35 (6.4%) and 59 (8.5%) for the DCB and DES group respectively. Kaplan Meier estimator plot did not show a significant difference between the groups. There was no difference between the groups in any of the secondary endpoints (cardiovascular mortality, ACS, stroke, major bleeding and TLR). Conclusion: Our real world data from a large, contemporary cohort of stable angina patients, including predominantly large vessels, demonstrate that DCB only angioplasty is safe compared to DES in terms of all major cardiovascular endpoints including TLR. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): B Braun - investigator initiated research